Analisis Pemanfaatan Ice Breaking Berbasis Konten Tiktok Dalam Pembelajaran Siswa Kelas III Di SDN Sawojajar 01 - Mardiana, Nana; Triputra, Dedi Romli; Sunarsih, Diah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the utilization of TikTok content-based ice breaking in the learning process of three-grade students at SDN Sawojajar 01 through a systematic literature review approach. The background of this research stems from the identification of problems including destructive student behavior during learning, the application of conventional and monotonous ice breaking methods, and the non-optimal use of audio-visual technology in classroom management. This research uses a qualitative method with a systematic literature review design. Data were collected from 15 relevant scientific articles published in 2019–2026, sourced from Google Scholar, Sinta-indexed journals, and Scopus-indexed journals, using the keywords ice breaking, TikTok, learning concentration, and elementary school. Articles were selected based on inclusion and exclusion criteria, then analyzed using content analysis techniques. The results of the literature review show: (1) ice breaking is theoretically proven to restore student concentration, reduce boredom, and increase learning participation; (2) TikTok as a short-form video platform has characteristics that are relevant to the learning style of Generation Alpha students and has been proven effective as an educational medium in various studies; and (3) the integration of TikTok content as an ice breaking instrument is projected to have positive implications for classroom dynamics, including a more dynamic classroom atmosphere, increased student concentration and participation, and strengthened teacher-student interaction. This study concludes that TikTok content-based ice breaking is theoretically feasible and promising as an innovative classroom management instrument for Generation Alpha elementary school students. Keywords: Ice Breaking, TikTok, Learning Concentration, Elementary School, Literature Review